Corporate social responsibility and supply chain management: Framing and pushing forward the debate. (10th November 2020) - Modak, Nikunja Mohan; Sinha, Sudipta; Raj, Alok; Panda, Shibaji; Merigó, José M.; Lopes de Sousa Jabbour, Ana Beatriz
Abstract: Corporate social responsibility (CSR) in supply chain management (SCM) is one of the burgeoning fields of the last decade. Significant interest in this area has led to a large number of publications in recent times. For this reason, this study has been carried out to provide a comprehensive framework and future research directions for this topic. This work presents a bibliometric analysis of relevant publications dealing with CSR in SCM up to April 2019. As well as the presentation of an overview of publications and citation structures, it also explores journals and countries based on a bibliometric study. To collect the relevant data for this study, we have utilized the reliable SCOPUS database. Our results highlight the significant contributions of journals, authors, universities, and countries on this topic. With the help of "Visualization of similarities (VOS)" viewer software, this study investigates bibliographic coupling of sources and countries. It also presents co-occurrence of keywords and graphic representations of the bibliographic materials. Finally, it provides an overview of all relevant review papers in this field and a comprehensive view of related research fields. Highlights: Bibliometric analysis has carried out of relevant publications dealing with CSR in supply chain management. Supply Chain Management: An International Journal and Journal of Cleaner Production have published more articles focusing on CSR and SCM jointly. The most cited articles are based on qualitative and theoretical research methods, aiming to propose frameworks.